2009
DOI: 10.1107/s0108270109001991
|View full text |Cite
|
Sign up to set email alerts
|

4′-[2-(2-Ethoxyethoxy)ethoxy]biphenyl-4-carboxylic acid: correlation between its crystalline and smectic phases

Abstract: The crystal structure of the dimeric title compound, C(19)H(22)O(5), is dominated by a head-to-head hydrogen-bonding interaction between centrosymmetrically related carboxyl groups in each monomer. The result is a dimeric axis of unusual length (ca 34 A), but still shorter than what could be expected for a fully extended chain, owing to two turning points in the oligoethoxy ends. This allows for an explanation of the structure of the smectic mesophase exhibited by this compound and at the same time fully valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The authors calculated l-values of 45.9 and 35.2 Ǻ for all-anti and some-gauche conformations, respectively, and suggested that the latter should be taken into account giving rise to a tilt angle of 28°rather than the 45°v alue calculated for the all-anti conformation. The structure of the mesogen in its crystalline phase, solved by SCXRD [43], confirmed the suggested gauche conformation with an end-to-end length of about 34 Ǻ and also revealed that the tilted lamellar structure is already present in the crystalline phase. In some cases, θ-values calculated for some SmC phases as described above were shorter than the optical tilt angle.…”
Section: Sc Crystallography In the Mesogen Crystalline Phase: Specifi...supporting
confidence: 60%
“…The authors calculated l-values of 45.9 and 35.2 Ǻ for all-anti and some-gauche conformations, respectively, and suggested that the latter should be taken into account giving rise to a tilt angle of 28°rather than the 45°v alue calculated for the all-anti conformation. The structure of the mesogen in its crystalline phase, solved by SCXRD [43], confirmed the suggested gauche conformation with an end-to-end length of about 34 Ǻ and also revealed that the tilted lamellar structure is already present in the crystalline phase. In some cases, θ-values calculated for some SmC phases as described above were shorter than the optical tilt angle.…”
Section: Sc Crystallography In the Mesogen Crystalline Phase: Specifi...supporting
confidence: 60%
“…The best evidence for this model was given by the single-crystal X-ray structure of 1a that we described in detail in another report, 9 which manifests two highly revealing features as can be seen in Figure 1. Firstly, it displays a smectic-type layered structure formed by dimers with head-to-head hydrogen-bonding interactions showing a strong micro-segregation between the aromatic moieties and the oxyethylene chains.…”
Section: Introductionmentioning
confidence: 69%